Analysis of Drug Management and Improvement Strategies Using the Hanlon Method at the Pharmacy Installation of Dr. Oen Kandang Sapi Hospital, Surakarta, Indonesia - Vidya Dharma, Cakka Kumara; Titik Sunarni; Ika Purwidyaningrum (HM Publisher, 2024)
Medication management is an important factor in ensuring the level of drug availability. The aim of this research is to analyze and provide strategies for improving drug management in the Pharmaceutical Installation of Dr. Oen Kandang Sapi Hospital Surakarta using the Hanlon method. This research uses a descriptive design, with data taken retrospectively and concurrently. Data was obtained from the selection, procurement, distribution, and use stages. In the selection stage, the results obtained were drug suitability with the National Formulary (65.14%) and suitability with the Hospital Formulary (75.07%); Procurement stage: frequency of procurement per year (96 times), frequency of delayed payments from hospitals (0 time). In the distribution stage, the percentage of expired date medicines damaged (0.15%), the accuracy of the data on the number of medicines on the stock card was (95.78%), and the percentage of dead stock (3.61%). Stage of use: number of items per prescription sheet (3.18 sheets), percentage of antibiotic drug prescriptions (8.53%), percentage of injection drug prescriptions (29.86%), the average time to serve prescriptions (non-concocted 8.88 minutes and concocted 17.52 minutes), the percentage of drugs that can be submitted (99.95%), percentage of drugs that are fully labeled (100%). Percentage of prescriptions with generic names (49.26%). The results of analysis using the Hanlon method show that drug management in the Pharmacy Installation of Dr. Oen Kandang Sapi Hospital Surakarta is quite good but needs to be improved continuously.